The Influence of Sustainability Report and Risk Management on Firm Value with Managerial Ability as a Moderating Variable - Tuwo, Lukman; Randa, Fransiskus; Raya, Christophorus Brainata Kevin (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – The purpose of the study is to examine the effect of managerial ability sustainability report and risk management on firm value. Design/methodology/approach – This research uses purposive sampling method in sample selection. The data sources in this study are annual reports and sustainability reports of manufacture companies listed on the Indonesia Stock Exchange for the period 2020 to 2022. Total of samples that met the criteria are 21 companies. The data collection method used is observation method. The study uses moderation regression analysis. Findings – The results show that sustainability report has a negative and no significant impact on firm value, risk management has a positive and significant impact on firm value, managerial ability to weakens the negative and no significant influence between the sustainability report and firm value, managerial ability strengthens the positive and significant influence between the risk management and firm value Originality – This research investigates the role of management in the relationship between sustainability reporting and risk management to the company's Keywords: Sustainability Report, Risk Management, Managerial Ability, Firm Value. Paper Type Research Result